EXPLORING OF PHYSICS CONCEPTS OF “SOUND WAVES” IN THE MORONENE TRIBE'S TAMBURU MUSICAL INSTRUMENT AS A PHYSICS LEARNING MATERIAL - NABA, SUL DAENG; KUSWANTO, HERU; KURNIAWAN, ARIS; ADRIANTO, NANANG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research investigates the physics concepts embedded in the traditional musical instrument